Answer:
1) The solution to the given equations is (3,6)
2) The solution to the given equations is (7,-1)
3) The solution to the given equations is (6,5)
Explanation:
1) Given equations are
![x+y=5\hfill (1)](https://img.qammunity.org/2021/formulas/mathematics/college/bclt5x01gnm3sb0etmy7vchvitks5rn8sk.png)
and
![x=1+y\hfill (2)](https://img.qammunity.org/2021/formulas/mathematics/college/nx58ujaicucyvtkg2m8cy3dm9oh7bha12w.png)
To solve the given equations by substitution method :
From equation (2) we have the value x=1+y
Substitute the value of x=1+y in equation (1) we get
(1+y)+y=5
1+y+y=5
1+2y=5
2y=5-1
2y=4
![y=(4)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/fwze5e9u7ejxo9oj524lf7n9gwyl4xerkk.png)
Therefore y=2
Now substitute the value of y=2 in equation (2) we get
x=1+y
x=1+2
Therefore x=3
The solution is (3,6)
2) Given equations are
![2x+3y=11\hfill (1)](https://img.qammunity.org/2021/formulas/mathematics/college/x2q3i5sz5vdllcwr5m2iwkzq77rw1s4whx.png)
and
![x+y=6\hfill (2)](https://img.qammunity.org/2021/formulas/mathematics/college/n5je7ld91j6lv2qceb6in5da4trdmmpf9z.png)
To solve the given equations by substitution method :
From equation (2) we have the value x=6-y
Substitute the value of x=6-y in equation (1) we get
2(6-y)+3y=11
12-2y+3y=11
y=11-12
Therefore y=-1
Now substitute the value of y=-1 in equation (2) we get
x+(-1)=6
x=6+1
Therefore x=7
The solution is (7,-1)
3) Given equations are
![x-y=1\hfill (1)](https://img.qammunity.org/2021/formulas/mathematics/college/u3unw5be03dcxvh9pme1wh6x86pl3wix4b.png)
and
![6x-7y=1\hfill (2)](https://img.qammunity.org/2021/formulas/mathematics/college/u8029tmspb80ym44t1zr0sk1yngmc22xqu.png)
To solve the given equations by substitution method :
From equation (1) we have the value x=1+y
Substitute the value of x=1+y in equation (2) we get
6(1+y)-7y=1
6+6y-7y=1
-y=1-6
Therefore y=5
Now substitute the value of y=5 in equation (1) we get
x-5=1
x=1+5
Therefore x=6
The solution is (6,5)